La cultura del stream y su relación con el aprendizaje del Diseño Gráfico - Andino Oñate, Lizeth Elizabeth (2023)
Nowadays, with technological advances, a large number of learning media have emerged, the problem is the lack of knowledge of these platforms that can help learning in the field of Graphic Design, also providing a possible source of work. The existence of these media is completely ignored, in addition to the little or no previous work on the subject. The present research will be devoted to assessing the use of new platforms and resources that can be used as means of learning or self-learning, specifically on the live streaming platform, Twitch. For the development of the research, a qualitative approach was used, using interviews with designers and people related to the world of communication. In addition, observation cards were assigned to outstanding figures in the world of the Twitch stream, which has a connection with graphic design. Furthermore, an exploratory design was included, since, being a recent and little studied topic, there is little information available. As a result of the research, a group of resources that are considered necessary to start in the world of the stream was determined.